HYPOSTATIC UNION AND THE SUBTLE BODY: AN ANALYSIS OF CHRISTIAN YOGIC PRACTICE - Schmalz, Mathew N (Asian Horizons, 2012)
The issue of Christian yogic practice has been central in discussion of Catholic adaptation to Indian culture. Sister Ishpriya once wrote that Christianity and Hinduism meet in “the cave of the heart,” a reference to a central yogic practice of seeing the heart not only as a silent place of refuge but as a microcosmic representation of the universe itself.1 Of course, Sister Vandana touched on many central yogic themes in her insightful reflections on the prayer of the name in the Hindu and Christian traditions.2 Father G. Gispert-Sauch has also explored the sacred syllable “Om” and its relation to Christian spirituality.3 More specifically, authors such as V.F. Vineeth and J.M. Dechanet have outlined specific aspects of what can be called “a Christian yoga” that assumes its formal shape from the yogic tradition proceeding from Patanjali but draws its content from Christian spiritual and scriptural reflection.4 Within the West, the development of Christian yoga has been seen as a central and suggestive aspect of the ashram and inculturation movements within Indian Catholicism.